1991
DOI: 10.1152/ajprenal.1991.261.5.f904
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation analysis of TGF-mediated oscillations in SNGFR

Abstract: Recent micropuncture studies in rats have demonstrated the existence of oscillatory states in nephron filtration mediated by tubuloglomerular feedback (TGF). We develop a minimal mathematical model of the TGF system, consisting of a first-order hyperbolic partial differential equation describing thick ascending limb (TAL) NaCl reabsorption and an empirical feedback relation. An analytic bifurcation analysis of this model provides fundamental insight into how oscillatory states depend on the physiological param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
141
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(154 citation statements)
references
References 9 publications
11
141
1
1
Order By: Relevance
“…Steady-state gain is the gain that has been measured in laboratory experiments; the concept of instantaneous gain arose from a theoretical analysis of a mathematical model of the TGF system (12,13). We have previously shown that, under restricted circumstances, G SS is closely approximated by Ϫ␥ (13).…”
Section: Concepts and Terminologymentioning
confidence: 99%
See 4 more Smart Citations
“…Steady-state gain is the gain that has been measured in laboratory experiments; the concept of instantaneous gain arose from a theoretical analysis of a mathematical model of the TGF system (12,13). We have previously shown that, under restricted circumstances, G SS is closely approximated by Ϫ␥ (13).…”
Section: Concepts and Terminologymentioning
confidence: 99%
“…For a sufficiently long delay in TGF signal transmission at the juxtaglomerular apparatus (JGA), the stability of a steady state is determined by the gain 1 ␥ and by the critical gain ␥ c (12). If ␥ Ͻ ␥ c , then the stable state is a (time-independent) steady state; if ␥ Ͼ ␥ c , then the stable state is an LCO.…”
Section: Concepts and Terminologymentioning
confidence: 99%
See 3 more Smart Citations